Utilization of Remittance for Rural People’s Needs: Study of Chhathar Rural Municipality of Dhankuta District - Adhikari, Dinesh (Rupantaran: A Multidisciplinary Journal, 2020)
Remittance is an enormous source of income for developing countries as well as Nepal. It contributes largely to the national economy in Nepal and it has also transformed the socio-economic lives of a large number of rural people. Number of remittance receiving household has reached more than 50 percent in the country. The remittances sent home by the migrants affect development of household, community and national levels. At the household level, remittances help to reduce poverty, improve living standard and attain educational needs. remittances could be used for entrepreneurship and productive investment which increases job opportunities and income of the people. Basic needs are fulfilled and released from landless or homeless condition by the use of remittance of rural people. Remittance inflows help to improve the lifestyle of rural people and their account position too. Many of the remittance used to consumption function or unproductive sector in rural area. It is suggested that policies and programs need to be developed for encouraging the utilization of remittances for productive use in order to promote rural growth.